Tantangan Integrasi Pajak dan Zakat dalam Kebijakan Fiskal - Anabilla Alma Widyaningtias; Diana Putri Utari; Devi Amalia; Mutiara Ramadhani; Dina Ainul Latifa; Asep Suryanto (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
The integration of taxes and zakat in fiscal policy is a strategic issue in Indonesia, a country with a Muslim majority and high dependence on tax revenue. Normatively, zakat has a function of distribution and poverty alleviation that is in line with the fiscal objectives of the state, namely allocation, distribution, and economic stabilization. However, in practice, the integration of the two has not been optimal and still leaves various complex structural and administrative problems. This study aims to analyze the regulatory, institutional, and social challenges in the integration of taxes and zakat and to formulate relevant and applicable fiscal policy implications in the context of national development. The study uses a literature review method with a descriptive qualitative approach based on secondary data from scientific journals, books, official reports, and current regulations. The results of the study show that the main obstacles lie in the differences in the legal basis between the sharia system and the national taxation system, the lack of integration between the data systems of the tax authorities and zakat institutions, low public literacy and compliance, and the large gap between the potential and actual collection of national zakat. Although zakat has been recognized as a tax-deductible expense, this mechanism has not significantly improved fiscal effectiveness or optimized welfare distribution. Integration based on regulatory harmonization, strengthening institutional governance, and digitizing administrative systems has the potential to strengthen welfare distribution, improve fiscal compliance, and support sustainable and inclusive national economic stability. Integrasi pajak dan zakat dalam kebijakan fiskal menjadi isu strategis di Indonesia sebagai negara dengan mayoritas penduduk Muslim dan ketergantungan tinggi pada penerimaan pajak. Secara normatif, zakat memiliki fungsi distribusi dan pengentasan kemiskinan yang selaras dengan tujuan fiskal negara, yaitu alokasi, distribusi, dan stabilisasi ekonomi. Namun, dalam praktiknya, integrasi keduanya belum berjalan optimal dan masih menyisakan berbagai persoalan struktural dan administratif yang kompleks. Penelitian ini bertujuan menganalisis tantangan regulasi, kelembagaan, dan sosial dalam integrasi pajak dan zakat serta merumuskan implikasi kebijakan fiskal yang relevan dan aplikatif dalam konteks pembangunan nasional. Penelitian menggunakan metode studi kepustakaan dengan pendekatan kualitatif deskriptif berbasis data sekunder dari jurnal ilmiah, buku, laporan resmi, serta regulasi terkini. Hasil kajian menunjukkan bahwa hambatan utama terletak pada perbedaan landasan hukum antara sistem syariah dan sistem perpajakan nasional, belum terintegrasinya sistem data antara otoritas pajak dan lembaga zakat, rendahnya literasi dan kepatuhan masyarakat, serta kesenjangan besar antara potensi dan realisasi penghimpunan zakat nasional. Meskipun zakat telah diakui sebagai pengurang penghasilan kena pajak, mekanisme tersebut belum signifikan meningkatkan efektivitas fiskal maupun optimalisasi distribusi kesejahteraan. Integrasi berbasis harmonisasi regulasi, penguatan tata kelola kelembagaan, serta digitalisasi sistem administrasi berpotensi memperkuat distribusi kesejahteraan, meningkatkan kepatuhan fiskal, serta mendukung stabilitas ekonomi nasional secara berkelanjutan dan inklusif.